IDENTIFICATION OF SPESIFIC DNA BANDS AND SIMILARITY LEVEL OF AROMATIC UPLAND RICE LINES AND CULTIVARS BASED ON RAPD - Arisetianingdih, Rita Eka Dessy (Universitas Jenderal Soedirman, 2012)
AbstractRandom Amplified Polymorphic DNA (RAPD) is one of molecular technique that can beused for DNA markers. RAPD gives better result, is more consistent, and is not influenced byenvironmental factors or growth phases than morphological characters. The research aimed foridentifiying specific DNA band and similarity level of tested rice lines and cultivars based onDNA band patterns of RAPD.DNA was extracted from single seed of rice by a modified CTAB DNA extractionmethod. The quantity and quality of extracted DNA was determined by agarose gelelectrophoresis and spectrophotometer. Result showed that the RAPD can differentiate alltested lines and cultivars. The RAPD revealed specific DNA band for Poso (OPA 9457), G12(OPA 91972), G13 (OPK 20227), G35 (OPA 9722), G39 (OPA 9341), Danau Tempe (OPK 10199 andOPA 244200) and Mentik Wangi (OPK 201487). Dendogram of genetic similarity showed that thelines closest to Mentik Wangi is G136, followed by G9, G10, G34, and G39. G12 hadsimilarity to Poso. G19 and G35 have similarity to Danau Tempe. Specific DNA band ofRAPD had a potential to be used as a tool for cultivar identification.Key words : Aromatic Upland Rice, RAPD, Cultivars Identification